2012
DOI: 10.1121/1.4733539
|View full text |Cite
|
Sign up to set email alerts
|

The effect of static pressure on the inertial cavitation threshold

Abstract: The amplitude of the acoustic pressure required to nucleate a gas or vapor bubble in a fluid, and to have that bubble undergo an inertial collapse, is termed the inertial cavitation threshold. The magnitude of the inertial cavitation threshold is typically limited by mechanisms other than homogeneous nucleation such that the theoretical maximum is never achieved. However, the onset of inertial cavitation can be suppressed by increasing the static pressure of the fluid. The inertial cavitation threshold was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 33 publications
3
29
0
2
Order By: Relevance
“…The overpressure acts to suppress cavitation and increase the amount of stored energy which leads to an increase in the collapse strength and therefore shock wave amplitudes. Besides, the cavitation threshold increases linearly with the static pressure, thus the acoustic pressure amplitude required to reach the cavitation threshold also increases [17]. Yasui et al [18] showed the optimal static pressure which maximizes the acoustic energy increases as the acoustic amplitude increases or viscosity of liquid decreases, which qualitatively agrees with Sauter et al [19].…”
Section: Effect Of Pressure On Sonication Efficacysupporting
confidence: 63%
“…The overpressure acts to suppress cavitation and increase the amount of stored energy which leads to an increase in the collapse strength and therefore shock wave amplitudes. Besides, the cavitation threshold increases linearly with the static pressure, thus the acoustic pressure amplitude required to reach the cavitation threshold also increases [17]. Yasui et al [18] showed the optimal static pressure which maximizes the acoustic energy increases as the acoustic amplitude increases or viscosity of liquid decreases, which qualitatively agrees with Sauter et al [19].…”
Section: Effect Of Pressure On Sonication Efficacysupporting
confidence: 63%
“…However, cavitation thresholds in even the purest sources of water (Herbert et al 2006; Bader et al 2012; Maxwell et al 2013) are much less than theoretically predicted (Church 2002). This discrepancy is generally attributed to nanometer-sized nuclei (Bader et al 2012; Maxwell et al 2013) that are difficult to extract from the medium (Flynn 1964). Such nuclei are however not likely to be found in-vivo due to the body’s natural filtration system.…”
Section: 2 Mechanisms Of Thrombolytic Enhancementmentioning
confidence: 80%
“…2 They are also the object of several concerns in medicine, such as the behaviour of microbubble contrast agent 3 or the dynamics of microbubbles in gas embolotherapy, 4 and in technology such as the spark assisted chemical engraving of glass 5 or the role of bubbles in the electroflotation process. 6 As a consequence, various mechanisms to produce bubbles using heat, 7 light, 8 ultrasounds, 9 capillary flow, 10 or electrolysis 11 as well as various sources able to deliver well defined bubbles [12][13][14][15] have been the object of recent studies especially in the microfluidics context. Here, we focus on the bubble production mechanism by water electrolysis and on the realization of a point source of bubbles based on this mechanism.…”
mentioning
confidence: 99%